Structure and Function of Cochlear Gap Junctions and Implications for the Translation of Cochlear Gene Therapies - Wu, Xuewen; Zhang, Wenjuan; Li, Yihui; Lin, Xi (Frontiers in Cellular Neuroscience, 2019)
Connexins (Cxs) are ubiquitous membrane proteins that are found throughout vertebrate organs, acting as building blocks of the gap junctions (GJs) known to play vital roles in the normal function of the cochlea. Mutations in Cx genes (particularly GJB2, which encodes Cx26), cause approximately half of all cases of congenital hearing loss in newborns. Great progress has been made in understanding GJ function and the molecular mechanisms surrounding the role of Cxs in the cochlea. Data reveal that multiple types of Cxs work together to ensure normal development and function of the cochlea. These findings include many aspects not proposed in the classic K+ recycling theory, such as the formation of normal cochlear morphology (e.g., the opening of the tunnel of Corti), the fine-tuning of the innervation of nerve fibers to the hair cells (HCs), the maturation of the ribbon synapses, and the initiation of the endocochlear potential (EP). New data, especially those collected from targeted manipulations of major Cx genes in the mouse cochlea, have demonstrated that Cx26 plays an essential role in the postnatal maturation of the cochlea. However, Cx26 and Cx30 assume very different roles in the EP generation, given that only Cx26 is required for normal hearing. This paper will review our current understanding on the molecular structure, cellular distribution, and major functions of cochlear GJs. Potential implications of the knowledge of cochlear GJs on the design and implementation of translational studies of cochlear gene therapies for Cx mutations are also discussed.